Dublin encounter - Davenport, Fionn (Lonely Planet, 2007)
Dublin is served by 87 low cost air routes including 24 from the UK. This work takes readers to the best events and festivals around. It also includes an Itineraries chapter that allows travellers to plan their time effectively. It also contains a detachable pull-out map.